Comparative analysis of IL-6 levels in post-tooth extraction inflammation among menopausal and non-menopausal: in vivo experimental - Parmasari, Wahyuni Dyah; Asyamsa Hidayat, Rheina Faticha; Rianti, Emilia Devi Dwi; Masfufatun, Masfufatun; Mokhtar, Siti Aisyah (Padjadjaran Journal of Dentistry, 2025)
Introduction: IL-6 acts as a biomarker of the inflammatory process. In elderly, especially women, the demand for tooth extraction treatment is quite high. A failure in the wound healing process during the menopausal period can prolong the inflammation process, thereby increasing the probability of infection, including alveolar osteitis. The menopausal process affects estrogen levels in the blood, which leads to reduced collagen formation as a key component of tissue regeneration. IL-6 levels can also increase during inflammation, especially in the chronic phase following tooth extraction. The study aims to analyze the differences in inflammatory IL-6 levels between menopausal and non-menopausal rats. Methods: This study applied an in vivo experimental design. A total of 30 Rattus novergicus were divided into two groups: a control group and a treatment group. The control group consisted of rats in which no oophorectomy was performed (non-menopausal), while the treatment group underwent ovariectomy to induce menopause. One after the procedure, tooth extraction were performed, and observations were conducted on days 3, 7, and 14 post-extractions. IL-6 levels were measured using ELISA from blood serum samples. The data were analyzed using One-Way ANOVA.  Results: The average IL-6 levels (in ng/L) in the control (non-menopausal) group on days 3, 7, and 14 were 0.087, 0.318, and 0.247, respectively. The average IL-6 levels in the treatment (menopausal) group were 0.191, 0.452, and 0.318, respectively. The One-Way ANOVA test showed no significant difference between the groups (p=0.799 > 0.05).  Conclusion: The trend of higher IL-6 levels in the menopausal group suggests a potential impact of hormonal changes on post-extraction inflammation. Although no significant difference was found, the elevated IL-6 levels in menopausal rats indicate a potential effect of estrogen deficiency on the inflammatory response following tooth extraction.